Treatment options and results of adjuvant treatment in nonmuscle-invasive bladder cancer (NMIBC) during the Bacillus Calmette–Guérin shortage. Issue 3 (May 2020) - Fankhauser, Christian Daniel; Teoh, Jeremy Yuen-Chun; Mostafid, Hugh
Abstract : Purpose of review: Given the worldwide shortage of Bacillus Calmette–Guérin (BCG), we review the efficacy of alternative BCG application schedules, doses or strains and intravesical chemotherapy in patients with nonmuscle-invasive bladder cancer (NMIBC). Recent findings: Modifying BCG schedules by reducing the dose is preferable to reducing the frequency of BCG that increases recurrence rates and should be avoided if possible. Changing the BCG substrain represents a reasonable option, as current evidence does not suggest different oncological outcomes with specific BCG substrains. Mitomycin C (MMC) alone is inferior to BCG with maintenance, but promising results have been demonstrated when used with chemohyperthermia and electromotive drug administration. Several other intravesical chemotherapies including Gemcitabine and Epirubicin should be used when both BCG and MMC are in short supply. Summary: In case of BCG shortage, much will depend on the severity and length of the BCG shortage, but our review supports several solutions: First, we recommend contacting the local pharmacist or BCG supplier to consider alternative BCG strains or sterile splitting of BCG doses. In the complete absence of BCG, consideration should be given to MMC with chemohyperthermia or electromotive drug administration where available or other intravesical chemotherapy. High-risk patients should be considered for cystectomy.